Size of the Canadian Breeding Population of Monarch Butterflies Is Driven by Factors Acting During Spring Migration and Recolonization - Crewe, Tara L.; Mitchell, Greg W.; Larrivée, Maxim (Frontiers in Ecology and Evolution, 2019)
The eastern North American monarch butterfly population shows a long-term population decline. While it is hypothesized that forest loss on the wintering grounds and milkweed loss throughout the breeding range are responsible for the observed decline, there is much less certainty regarding the factors driving year-to-year variation around the current population level. Using 15 years of butterfly count data, we used a community-based approach to delineate the stage of the annual cycle during which population limiting factors are most strongly acting. We compared annual fluctuations in size of the breeding population of monarch butterflies in Canada to fluctuations in 13 additional butterfly species which either migrate long distances to Canada or are resident but breed in similar habitats to the monarch. We show that the breeding population of monarchs in southern Canada shows a higher degree of synchrony with other long-distance migrants than with breeding residents, and that annual fluctuations of all migrant butterflies show a positive correlation with the number of 21 ˚C days during spring migration and re-colonization. Further, we found that size of the monarch breeding population shows a higher degree of synchrony with the size of the following winter population than with the size of the previous winter population. Combined, our results suggest that the monarch population in Canada is limited by factors acting during spring migration, and that weather plays an important role in the ability of the monarch to successfully re-colonize and breed in the northern portion of their summer range each year. A predicted increase in temperature in the early spring, combined with continued loss of breeding and wintering habitat, has the potential to limit the reproductive capacity of monarchs and their ability to recover from population lows.